Peran Komunikasi Guru dalam Resolusi Konflik Interpersonal Antar Siswa - Salsabina. S, Laila; Sumayyah, Lia; Sagala, Ardin Rizky Andre; Manurung, Afwan Syahril (ETHNOGRAPHY: Journal of Design, Social Sciences and Humanistic Studies, 2024)
The role of teacher communication in resolving interpersonal conflicts between students is an important aspect in creating a harmonious and conducive school environment for the learning process. Conflicts between students often occur at school, either due to differences of opinion, behavior, or social competition. In this case, teachers function as mediators who not only identify the source of the conflict, but also manage and resolve the conflict through effective communication. This study aims to examine the role of teacher communication in resolving interpersonal conflicts between students and how the communication approach used can affect the conflict resolution process. The method used in this study is library research. The results of the study show that open, empathetic, and constructive communication from teachers can help students understand their respective perspectives and find adequate solutions. In addition, the teacher's ability to listen, give positive feedback, and use appropriate mediation techniques has proven to be effective in relieving tension and reducing the possibility of recurrence of conflicts in the future. This study concludes that good and structured communication from teachers is very important in maintaining relationships between students and supporting the creation of a more harmonious learning atmosphere in schools.